Bioceramic Coatings for Metallic Implants - Vladesku A. Alina; Surmeneva M. A. Maria Alexandrovna; Kotrut M. K. Mikhay Kosmin; Surmenev R. A. Roman Anatolievich; Antoniac I. V. Iulian Vasile (2016, 2016)
Title screen